2021
DOI: 10.1177/19476035211007919
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol and Apolipoprotein A1 in Synovial Fluid: Potential Predictors of Disease Severity of Primary Knee Osteoarthritis

Abstract: Objectives The aim of this study was to detect levels of common lipid species in serum and synovial fluid (SF) of primary knee osteoarthritis (OA) patients and investigate their correlations with disease severity. Materials and Methods The study enrolled 184 OA patients receiving arthroscopic debridement or total knee arthroplasty and 180 healthy controls between April 2012 and March 2018. Total triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
6
16
1
Order By: Relevance
“…However, after lipid adjustment, the concentrations were similar to the baseline values. Similar studies were conducted by Zhang et al (2021) [ 23 ] who analyzed both high-density lipoprotein cholesterol and apolipoprotein A1 in the synovial fluid as potential prognostic factors for the severity of primary osteoarthritis of the knee. The study included 184 patients with osteoarthritis who received arthroscopic debridement or total knee arthroplasty, and 180 healthy controls.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…However, after lipid adjustment, the concentrations were similar to the baseline values. Similar studies were conducted by Zhang et al (2021) [ 23 ] who analyzed both high-density lipoprotein cholesterol and apolipoprotein A1 in the synovial fluid as potential prognostic factors for the severity of primary osteoarthritis of the knee. The study included 184 patients with osteoarthritis who received arthroscopic debridement or total knee arthroplasty, and 180 healthy controls.…”
Section: Resultssupporting
confidence: 58%
“…Any significant differences were not determined in serum TG and ApoB concentrations between both groups, while primary knee osteoarthritis patients had higher TC and LDL-C levels, and lower HDL-C and ApoA1 levels ( p < 0.05). HDL-C and ApoA1 levels in synovial fluid were negatively correlated with cartilage damage, radiographic severity, and symptomatic severity of primary knee OA; therefore, the authors suggest that these factors be considered potential biological markers [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, administration of atorvastatin can suppress the development of both OA and atherosclerosis, whereas ezetimibe only has an effect on atherosclerosis. It was found that lipid deposits in osteoarthritic cartilage and chondrocytes at an early stage of OA, which may trigger the development of OA (32). In addition, oxidized LDL participates in cartilage destruction by activating synovial cells, thereby promoting the release of growth factors and proinflammatory cytokines (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of dyslipidemia in the pathogenesis of OA is still missing, the hypothesis is that lipid deposition in the joint may trigger OA development, on the basis of findings that substantial lipid deposits in osteoarthritic cartilage and chondrocytes at an early stage of OA before apparent histological changes [ 20 ]. Also, higher total and non-HDL cholesterol were associated with increased cartilage degeneration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%